2020
DOI: 10.29228/turkishstudies.39646
|View full text |Cite
|
Sign up to set email alerts
|

Çevrimiçi Değerlendirme Sistemlerinin Eğitimde Kullanımı: Bir İçerik Analizi

Abstract: With the spread of technological innovations in education, it is seen that studies on online evaluation systems that are a part of distance education have intensified in recent years. Online evaluation systems can be defined as systems where questions are transmitted to students via the internet and answers are given using mouse and keyboard. This study aims to evaluate the studies conducted on the online evaluation system with the content analysis method. In this context, between the years of 1987-2018, OPAC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Additionally, students report that they feel more comfortable, fast, productive, and secure in online exams than traditional exams (Saban et al, 2010). There are also particular limitations and disadvantages of online testing, such as the requirement of a computer and internet access, safety issues surrounding online exam cheating, and some communication problems (Arslan & Yetgin, 2020;Anderson et al, 2005, as cited in Sırakaya et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, students report that they feel more comfortable, fast, productive, and secure in online exams than traditional exams (Saban et al, 2010). There are also particular limitations and disadvantages of online testing, such as the requirement of a computer and internet access, safety issues surrounding online exam cheating, and some communication problems (Arslan & Yetgin, 2020;Anderson et al, 2005, as cited in Sırakaya et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The e-assessment system has been an alternative method even before the Covid 19 pandemic, and there is vast quantitative and qualitative literature dealing with different dimensions of online testing. For example, in a content analysis study by Arslan and Yetgin (2020), who reviewed the studies on the online assessment between 1987 and 2018, it was found that there were many papers on students' attitudes and opinions towards online examinations and online exam systems (Yenilmez et al, 2005, Yağcı et al, 2015, online assessment and evaluation (Callı et al, 2003;Battal et al, 2010;Nguyen et al, 2017), reliability of online exams (Gül & Doğan, 2011;Sakal & Güvenç, 2016;Keskin & Güneş, 2015), and testing modality and its effects (Alexander et al, 2001;Clariana and Wallace 2002;Oduntan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%